Non-coding transcriptome profiles in clear-cell renal cell carcinoma - Tesarova, Tereza; Fiala, Ondrej; Hora, Milan; Vaclavikova, Radka (Nature reviews. Urology, 2025)
Clear-cell renal cell carcinoma (ccRCC) is a common urological malignancy with an increasing incidence. The development of molecular biomarkers that can predict the response to treatment and guide personalized therapy selection would substantially improve patient outcomes. Dysregulation of non-coding RNA (ncRNA) has been shown to have a role in the pathogenesis of ccRCC. Thus, an increasing number of studies are being carried out with a focus on the identification of ncRNA biomarkers in ccRCC tissue samples and the connection of these markers with patients' prognosis, pathological stage and grade (including metastatic potential), and therapy outcome. RNA sequencing analysis led to the identification of several ncRNA biomarkers that are dysregulated in ccRCC and might have a role in ccRCC development. These ncRNAs have the potential to be prognostic and predictive biomarkers for ccRCC, with prospective applications in personalized treatment selection. Research on ncRNA biomarkers in ccRCC is advancing, but clinical implementation remains preliminary owing to challenges in validation, standardization and reproducibility. Comprehensive studies and integration of ncRNAs into clinical trials are essential to accelerate the clinical use of these biomarkers.
Keywords: RNA, Untranslated; Biomarkers, Tumor; nekódující RNA; Carcinoma, Renal Cell; prognóza; nádory ledvin; nádorové biomarkery; karcinom z renálních buněk; Humans; Transcriptome; Kidney Neoplasms; Prognosis; lidé; transkriptom